Alterações imunoinflamatórias dos tecidos periodontais de pacientes com a Covid-19 em uma unidade de terapia intensiva - Popiolek, Isabela Mangue (2022)
Recent researches shows that in patients with Covid-19 and elevated inflammatory cytokines, postmortem pathology revealed tissue necrosis and interstitial macrophages, as well as monocyte infiltrations in lungs, heart, and gastrointestinal mucosa. In addition, severe lymphopenia with pro-inflammatory T-cell hyperactivity and decreased regulatory T-cells is commonly seen in critical patients – findings that suggest a dysregulated immune response. Considering that Interleukin-6 (IL-6) plays a key role in periodontal pathogenesis, stimulating the production of acute inflammatory substances, and was significantly high in patients with SARS-CoV-2, it is necessary to understand the relationship between Periodontal Disease (PD) and the infection caused by the new coronavirus. Therefore, the objective of this study was to evaluate the immunoinflammatory aspect of periodontal tissues of patients with Covid-19 admitted to the ICU of the Western Paraná University Hospital, in the city of Cascavel-PR. This is a cross-sectional case-control study, classified as observational and exploratory. Patients were divided into two groups: G1 (Case n=50): with respiratory failure with a positive diagnosis for Covid-19 and G2 (Control n=28): with respiratory failure with a negative diagnosis for Covid-19. Patients were evaluated with intraoral clinical examination, focusing on the diagnosis of periodontal alterations, considering the parameters: Gingival Level (GL), Probing Depth (PD), Bleeding on Probing (BP) and Clinical Attachment Level (CAL). Hematological exams were also carried out and Gingival Crevicular Fluid (GCF) was collected to determine the amount of fluid absorbed in mm2 and the presence of IL-6. To determine if periodontal changes would be risk or aggravating factors for Covid-19, and vice versa, the data were matched using the Propensity Score. It was found that most patients in G1 were male (64%) and the most prevalent age in this group was between 41 and 50 years (32%). Regarding periodontal parameters, patients with Covid-19 had lower BP and PD and higher amounts of GCF (about CAL, there was no difference between the groups). Regarding blood tests, patients with Covid-19 had higher amounts of hemoglobin, erythrocytes, neutrophils and platelets, in addition to statistically significant differences in the frequency of administration of antibacterials and corticosteroids. It was possible to verify a more accentuated inflammatory profile in patients with Covid-19, due to the increase in the amount of GCF. Regarding the amount of IL-6 in the GCF, there was no difference between the groups, although a trend of increased cytokines associated with SARS-CoV-2 infection was observed. The importance of more clinical studies, with larger sample groups, is highlighted to better clarify the exposed results and elucidate the association between PD and Covid-19.